Optimasi Sistem Distribusi Sumber Air Mineral dan Pemberdayaan Masyarakat Dengan Integrasi Sumber Daya Alam Sebagai Akselerator Perekonomian Desa Polengan - Adi Pratama, Rohmawan; Abelita Risanti, Ramadhani; Efendy Yusuf, Gilang; Rofius Syan, Mohammad; Kusuma Wardani, Feriana (LPPM Universitas Trunojoyo Madura, 2024)
Polengan Village has abundant natural resource potential, but the village community has not been able to fully optimize the potential of existing resources in the village. One of the causes is the lack of understanding and awareness among village communities about developing their existing potential. The aim of this activity is to analyze village natural resources for sustainable development, analyze the development and processing of village water resources, as well as increase community knowledge about technological developments and provide creative ideas for optimizing natural resources in the village. The method used for this activity is carried out offline in the form of installing tools to manage water sources into water suitable for consumption. This village community empowerment program contributes to holding special training on product branding to provide added value to products and attract customers' buying interest. The results of this community empowerment show an increase in public understanding regarding product branding. Sustainable production and management of Tirta Polengan drinking water sources anddistribution can improve the economy of village communities and the community's ability to manage existing natural resources. The marketing strategy program in the form of videography content and product photography is able to increase people's creativity and innovation in developing products in the form of AMDK. So as to create a workforce that is competent in utilizing village natural resources into superior products and collaborating with external parties to develop the business.